Analysis of PCR as a tool for detection of JC virus DNA in cerebrospinal fluid for diagnosis of progressive multifocal leukoencephalopathy. - Hammarin, A L (1996)
Two polyomaviruses, JC virus (JCV) and BK virus (BKV), affect humans. JCV is the causative agent of progressive multifocal leukoencephalopathy (PML), and detection of JCV in the central nervous system (CNS) is a prerequisite for confirmation of the disease. BKV is generally not associated with neurological disease, but involvement of BKV in patients with CNS disorders has been reported. In the present study polyomavirus DNA was detected by a nested PCR at a sensitivity corresponding to the detection of 10 copies of JCV DNA in 10 microliters of cerebrospinal fluid (CSF). CSF samples from 212 patients with neurological symptoms and immunodeficiencies were investigated for the presence of polyomavirus DNA. Of 128 human immunodeficiency virus (HIV)-infected patients, 14 (11%) had JCV DNA in their CSF, and all 14 patients had clinical PML. BKV DNA was detected in one HIV-infected patient with neurological symptoms not compatible with PML. Among 84 HIV-negative patients, 6 (7%) had detectable JCV DNA in their CSF, confirming PML in patients with clinical conditions of T-cell lymphoma, chronic lymphatic leukemia, status postliver transplantation, congenital immunodeficiency, sarcoidosis, and immunodeficiency of unknown origin. The specificity of the PCR was confirmed by a clinical follow-up study which showed full agreement between the detection of JCV DNA in CSF and clinically manifest PML. The described PCR is a rapid, reproducible, and easily performed assay.